Metodologias de aplicação de sulfonamida heterocíclica no controle de Meloidogyne javanica e Pratylenchus brachyurus em soja - Oriani, Eduardo Elias [UNESP] (2015)
Problems with nematodes have been increasing on soybeans fields. Programs for nematode population reduction are essential to reduce yield losses. Three application methodologies, using the novel sulfonamide nematicide, were tested to control M. javanica e P. brachyurus in soybean: 1) furrow application at sowing planting 2) broadcast application in the total area 5 days before planting, 3) furrow application at sowing and an additional total area application 20 days after emergence (DAE). Evaluations consisted in: i) number of plants per linear meter (14 DAE); ii) plants height and fresh weight of shoots (45 and 90 DAE); iii) nematode population of different developmental stages (eggs, juveniles and adults) in the roots (45 and 90 DAE); iv) gall index (45 and 90 DAE); v) yield. Among tested methodologies, sulfonamide nematicide furrow application at sowing presented M. javanica population reduction 45 DAE with 1.500 g a.i/ha and with 2.000 g a.i/ha was detected population reduction 90 DAE. This methodology did not reduce P. brachyurus population in any of the doses tested. The second methodology, with application in the total area 5 days before planting, reduced M. javanica population with 500 and 1.500 g a.i/ha 90 DAE. This methodology also reduced P. brachyurus with 1.500 g a.i/ha 45 DAE. The third methodology, sulfonamide nematicide furrow application at sowing (150 g a.i/ha) and an additional total area application 20 DAE (750 g a.i/ha) significantly reduced M. javanica population until 45 DAE and showed gall index reduction until 90 DAE. This methodology also did not have any effect on P. brachyurus population in any of the doses tested. In all methodologies tested the sulfonamide did not show negative crop response, did not increase the plant height, fresh weight and yield